Rational Design of a Laminated Dual-Polymer/Polymer–Ceramic Composite Electrolyte for High-Voltage All-Solid-State Lithium Batteries - Yu, Xingwen; Li, Jianyu; Manthiram, Arumugam (ACS materials letters, 2020)
We present a multi-layer approach to design a laminated dual-polymer/polymer–ceramic composite electrolyte (LDPPCCE) for high-voltage all-solid-state lithium batteries. An anode friendly poly(ethylene oxide) (PEO) serves as a matrix to face the Li-metal anode. To enhance the room-temperature Li+-ion conductivity, succinonitrile (SN) is incorporated into the PEO. At the cathode side, an oxidation tolerant poly(acrylonitrile) (PAN) matrix is employed. To enhance the ionic conductivity and suppress lithium dendrite, NASICON-type lithium aluminum titanium phosphate (Li1+x Al x Ti2–x (PO4)3, LATP) powder is integrated into the PAN. The PEO-SN dual-polymer and the PAN-LATP composite deliver matched ionic conductivity. Uniting the two electrolyte layers, the resulting elastic LDPPCCE exhibits an ionic conductivity of 1.31 × 10–4 S cm–1 at ambient temperature with an electrochemical stability window of 0–5 V. All-solid-state lithium cells, fabricated with the LDPPCCE electrolyte, high-capacity/high-voltage LiNi0.8Co0.1Mn0.1O2 cathode, and lithium–metal anode exhibit exceptional electrochemical performance with a long cycle life.